Effect of Type-I Interferon on Retroviruses - Ana Doménech; Guadalupe Miró; Esperanza Gómez-Lucía; Victorio M. Collado (Viruses, 2009)
Type-I interferons (IFN-I) play an important role in the innate immune response to several retroviruses. They seem to be effective in controlling the in vivo infection, though many of the clinical signs of retroviral infection may be due to their continual presence which over-stimulates the immune system and activates apoptosis. IFN-I not only affect the immune system, but also operate directly on virus replication. Most data suggest that the in vitro treatment with IFN-I of retrovirus infected cells inhibits the final stages of virogenesis, avoiding the correct assembly of viral particles and their budding, even though the mechanism is not well understood. However, in some retroviruses IFN-I may also act at a previous stage as some retroviral LTRs posses sequences homologous to the IFNstimulated response element (ISRE). When stimulated, ISREs control viral transcription. HIV-1 displays several mechanisms for evading IFN-I, such as through Tat and Nef. Besides IFN-α and IFN-β, some other type I IFN, such as IFN-τ and IFN-ω, have potent antiviral activity and are promising treatment drugs.